Diversity and Distribution of Rust Fungi in Central Himalayan Region - Palni, Anwesha sah singh* and Uma Tiwari (Journal of Phytology, 2011)
An extensive field survey was made during 2007 to 2008 in Nainital (Uttaranchal) for rust diseases of wild plants. In all 12 genera of rust fungi with 35 species belonging to 7 families were collected and identified. Among these, one genus Aecidium Pers. ex. Pers. was an anamorphic and 11 were holomorphic. Most of the rust fungi were collected from herbaceous and shrubby hosts, while few were found to be pathogens of tree species. Populus nigra var. italica, and an extensive cultivated tree in this area was found to be a new host for the rust fungus Melampsora ciliata Barclay. The study suggest further exploration of the area for rust disease in order to assess the diversity of these fungi particularly in ferns, grasses, sedges and trees including cultivated ones. Key words: Diversity, Taxonomic Description, Rust Fungi, Central Himalaya <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Anwesha Singh and Uma Tiwari Palni. Diversity and Distribution of Rust Fungi in Central Himalayan Region. J Phytol 3/2 (2011) 49-59